Diagnostic Imaging Performance of Dual-Energy Computed Tomography Compared with Conventional Computed Tomography and Magnetic Resonance Imaging for Uterine Cervical Cancer - Saki Shibuki; Tsukasa Saida; Kensaku Mori; Toshitaka Ishiguro; Taishi Amano; Miki Yoshida; Mariko Miyata; Toyomi Satoh; Takahito Nakajima (Indian Journal of Radiology and Imaging, 2024)
Objective This article evaluates the ability of low-energy (40 keV) virtual monoenergetic images (VMIs) in the local diagnosis of cervical cancer compared with that of conventional computed tomography (C-CT) and magnetic resonance imaging (MRI), using clinicopathologic staging as a reference.